Brain–computer interface devices for patients with paralysis and amputation: a meeting report. (29th February 2016) - Bowsher, K; Civillico, E F; Coburn, J; Collinger, J; Contreras-Vidal, J L; Denison, T; Donoghue, J; French, J; Getzoff, N; Hochberg, L R; Hoffmann, M; Judy, J; et al.
Abstract: Objective . The Food and Drug Administration's (FDA) Center for Devices and Radiological Health (CDRH) believes it is important to help stakeholders (e.g., manufacturers, health-care professionals, patients, patient advocates, academia, and other government agencies) navigate the regulatory landscape for medical devices. For innovative devices involving brain–computer interfaces, this is particularly important. Approach . Towards this goal, on 21 November, 2014, CDRH held an open public workshop on its White Oak, MD campus with the aim of fostering an open discussion on the scientific and clinical considerations associated with the development of brain–computer interface (BCI) devices, defined for the purposes of this workshop as neuroprostheses that interface with the central or peripheral nervous system to restore lost motor or sensory capabilities. Main results . This paper summarizes the presentations and discussions from that workshop. Significance . CDRH plans to use this information to develop regulatory considerations that will promote innovation while maintaining appropriate patient protections. FDA plans to build on advances in regulatory science and input provided in this workshop to develop guidance that provides recommendations for premarket submissions for BCI devices. These proceedings will be a resource for the BCI community during the development of medical devices for consumers.